Relationship Between Rate of Smartphone Addiction and Incidence of Digital Eye Strain in Adolescents - Meilyana, Berna Detha; B, Nofriadi; Setyawan, Arif; Suroso, Heri; S, Hanifuddin Dwi; Ekwantoro, Ekwantoro (STIKES Adi Husada, 2025)
The impact of the COVID-19 pandemic has had a big impact on the world of education. Because of online learning, smartphones have a very important role in meeting these needs. Smartphones have a negative impact that can be felt by students when used in their continuous learning is Digital Eye Strain (DES) or often referred to as eye fatigue. This study aims to determine the relationship between the rate of smartphone addiction and the incidence of digital eye strain in adolescents aged 13 – 15 years at Yohanes Gabriel Pare Junior High School. This study used a cross-sectional design. The sample selection used purposive sampling with a total of 115 respondents. The research was conducted using DES questionnaires. The results of the Kendall's Tau test showed that the correlation test results were known to have a significance value, or Sig. (2-tailed), between the variable level of smartphone addiction and the incidence of DES was 0.001. While the correlation is significant at 0.05, the value is 0.001 < 0.05. There is a significant relationship between the level of smartphone addiction and the incidence of digital eye strain in adolescents aged 13-15 years at Yohanes Gabriel Pare Junior High School. Smartphone addiction can affect eye function. The duration and frequency of prolonged smartphone use can affect dry eyes, redness, and the onset of DES symptoms.